The therapeutic effect and mechanism of melatonin on osteoarthritis: From the perspective of non-coding RNAs - Li, Shuai; Si, Haibo; Xu, Jiawen; Liu, Yuan; Shen, Bin (Frontiers in Genetics, 2022)
Osteoarthritis (OA) is a slowly progressing and irreversible joint disease. The existing non-surgical treatment can only delay its progress, making the early treatment of OA a research hotspot in recent years. Melatonin, a neurohormone mainly secreted by the pineal gland, has a variety of regulatory functions in different organs, and numerous studies have confirmed its therapeutic effect on OA. Non-coding RNAs (ncRNAs) constitute the majority of the human transcribed genome. Various ncRNAs show significant differentially expressed between healthy people and OA patients. ncRNAs play diverse roles in many cellular processes and have been implicated in many pathological conditions, especially OA. Interestingly, the latest research found a close interaction between ncRNAs and melatonin in regulating the pathogenesis of OA. This review discusses the current understanding of the melatonin-mediated modulation of ncRNAs in the early stage of OA. We also delineate the potential link between rhythm genes and ncRNAs in chondrocytes. This review will serve as a solid foundation to formulate ideas for future mechanistic studies on the therapeutic potential of melatonin and ncRNAs in OA and better explore the emerging functions of the ncRNAs.